Thrombin inhibition and cisplatin block tumor progression in ovarian cancer by alleviating the immunosuppressive microenvironment - Alexander, Eric T. (Oncotarget, 2016)
Cancer is often associated with an increased risk of thrombotic complications which can be aggravated by treatment with chemotherapeutics such as cisplatin. Multiple lines of evidence suggest that thrombin activity promotes tumor growth and metastasis. We examined the effect of co-treatment with dabigatran etexilate, a direct thrombin inhibitor, and cisplatin using the murine ID8 ovarian cancer model. Mice receiving co-treatment with both dabigatran etexilate and low dose cisplatin had significantly smaller tumors, developed less ascites and had lower levels of circulating activated platelets and tissue factor (TF) positive microparticles than those treated with dabigatran etexilate or cisplatin alone. Co-treatment with dabigatran etexilate and cisplatin significantly decreased the number of Gr1(+)/CD11b(+) myeloid derived suppresser cells and CD11b(+)/CD11c(+) dendritic cells in the ascites of ID8 tumor-bearing mice. Co-treatment also significantly reduced levels of pro-tumorigenic cytokines including TGF-β, VEGF, IL-6, IL-10, and MCP-1 in the ascites while increasing IFN-γ production by CD8(+) effector T cells in the tumor ascites. These results demonstrate that co-treatment with dabigatran etexilate significantly augments the anti-tumor activity of cisplatin in ovarian tumor progression by alleviating the immunosuppressive microenvironment, suggesting that thrombin may be a potential therapeutic target for treatment of ovarian cancer.